A Rapid, Affordable and Feasible Method for Detection of the HBG1: g.-225_-222delAGCA Polymorphism. (4th July 2018) - Musso, Marco; Luca Forni, Gian
Abstract: Single point mutations or small deletions in the A γ - and G γ-globin gene promoter region are associated to the nondeletional hereditary persistence of fetal hemoglobin (HPFH). Currently, DNA sequencing is most common technique adopted for detection of hemoglobin (Hb) mutations. However, some can be rapidly detected because they either destroy or create a recognition site for a restriction enzyme. Here we show that the 4 bp deletion, HBG1 : g.-225_-222delAGCA in the A γ-globin gene promoter can be easily detected using the Tru 1I ( Mse I) restriction enzyme that cuts only in the absence of this deletion. This approach utilizes ordinary instrumentations (thermocycler and agarose gel electrophoresis) available in any basic molecular genetics laboratory, providing a reliable and inexpensive method of genetic screening.